Guaiane sesquiterpenes from Lindera glauca: isolation, structural elucidation, and hepatoprotective effect - Lan-Lan Nie; Xin-Yu Sun; Qing Shi; Ya-Nan Duan; Jia-Yun Yang; Jin-Chang Huang; Xin-Wen Zhang; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2026)

Pixel-wise change detection for tunnel linings from multi-temporal inspections - Yi Hu; Chenxi Xue; Ziyan Yang; Zhengwen Xu; Lianbi Yao; Lujing Yang; Qing Ai (Tunnelling and Underground Space Technology, 2026)

Seismic damage-state classification of prefabricated steel pipe pile–supported wharves using a global lateral stiffness reduction indicator - Jingsong Huang; Qing AI; Lulu Zhang; Yinghui Tian; Shouji Du; Yanping Zhu (Engineering Structures, 2026)

Research progress on radon migration in porous media - Meng-Jie Li; Yan-Shi Xie; Bo-Yang Wang; Ao-Xue Tang; Shi-Li Han; Zheng-Qing Wang; Hai-Yang He; Shan Liu; Guo-Liang Ai (Journal of Environmental Radioactivity, 2026)

Core–shell hard carbon with enriched closed pores and controlled defects for enhanced sodium-ion battery performance - Qing Zhou; Chunfei Shi; Zicheng Wang; Hao Ai; Kaifeng Du (Chemical Engineering Journal, 2026)

K-DPSA: A hierarchical surrogate-assisted evolutionary algorithm for expensive constrained multi-objective optimization with application to UAV path planning - Ai-Qing Tian; Fei-Fei Liu; Shao-Quan Ni; Jeng-Shyang Pan (Swarm and Evolutionary Computation, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Pesticide beta-cypermethrin impairs endometrial decidualization and embryo implantation by suppressing autophagy through oxidative stress - Li-Qing Wang; Huang-Nian You; Qiong-Jun Xu; Wen-Jie Yu; Xiao-Mei Wu; Xiao-Qing Pang; Xiao-Xi Chen; Wen-Bin Du; Qian-Feng Qiao; Jing-Ai Li; Yu-Meng Zhou; Yong-Jiang Zhou (Chemico-Biological Interactions, 2026)

Revealing the roles of biochar in anaerobic digestion of waste activated sludge with the overloading accumulation of humic acids - Wen-Tao Li; Fei Wang; Qing-Bin Meng; Sheng-Jie Sun; Cong-Cong Tang; Lei Yang; Jun Lan; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhang-Wei He (Journal of Water Process Engineering, 2026)

Analysis of genetic diversity and population structure in Shaoyang tea plants (Camellia sinensis) utilizing KASP markers and SNP loci - Jin Li; Xiao-Yan Qiu; Chang-Qing Xie; Han Tang; Ai-Ming Tang; Jun Tang (Genetic Resources and Crop Evolution, 2026)

Data-physics integration model for predicting tunnel convergence subject to water level fluctuations and lining structure degradation - Junjie Liu; Qing Ai; Lulu Zhang; Junyi Zhu; Hui Wang; Xingchun Huang; Yong Yuan (Tunnelling and Underground Space Technology, 2026)

Insights to how tubular pore biochar affects anaerobic digestion of waste activated sludge: Performances and mechanisms - Ze-Mu Li; Ai-Hua Li; Qing-Bin Meng; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Vascular endothelial growth factor (VEGF)-related blood flow regulation and anti-inflammation in the protection of Danzhu Fuyuan Granules against cognitive impairment - Yu Duan; De-Wei Zhu; Qin Liu; Xing-Yuan Li; Xiao-Ting Zhou; Jing-Qing Hu; Ai-Jun Liu (Metabolic Brain Disease, 2026)

Aerobic denitrification coupled with iron-carbon micro-electrolysis to enhance synchronous removal of nitrogen and phosphorus in wetlands - Wei-Yi Shi; Wen-Huai Wang; Bo-Wen Liu; Jun-Yu Ai; Qing-Yuan Tian; Yi Wang (Bioresource Technology, 2026)

Study on the dynamic interaction between buried bent pipes and soil under the influence of oblique incidence of SV waves - Chang-lu Xu; De-long Huang; Hui-yue Wang; Sha-sha Yu; Huan-qing Song; Hang Cen; Zi-yuan Huang; Qiang Liu; Ai-ping Tang (Soil Dynamics and Earthquake Engineering, 2026)

Enzymatic stoichiometry as a reliable proxy for evaluating microbial nutrient limitation in lentic sediments and phosphorus-enriched soils: A meta-analysis - Ling AI; Ting QING; Fuzhong WU; Meilin XUAN; Kai YUE; Xiangyin NI (Pedosphere, 2026)

A new sponge (Ascospongiae) from the early Cambrian Guanshan Biota - Lin-Jun Zou; Joseph P. Botting; Jie Yang; Xiao-Yu Yang; Wei Li; Qing-Hao Guo; Yu Wang; Chun-Li Li; Xi-Guang Zhang; Ai-Lin Chen (Palaeoworld, 2026)

Effects of phyllosphere and rhizosphere microbes on intraspecific competition of the invasive plant Ageratina adenophora and native plants - Zi-Qing Liu; Zhao-Ying Zeng; Ai-Ling Yang; Yong-Lan Wang; Chao Zhao; Han-Bo Zhang (Plant and Soil, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

Magnetic aptasensor with UiO-MOFs-mediated orientation-ordered aptamers for sensitive portable test of okadaic acid toxin - Qing'ai Chen; Yuwei Zhou; Guobin Huang; Chenchen Lin; Xucong Lin (Analytica Chimica Acta, 2026)

Structure-oriented molecular extension strategies unlock C-glycoside insecticides targeting OfChtII and OfHex1 - Yin Ai; Yanjun Zhang; Wei Chen; Xingyue Zhou; Yanhong Dong; Qing Yang; Jianjun Zhang (Pesticide Biochemistry and Physiology, 2026)

Synergistic enhancement of tetracycline photodegradation in 5 % Ce-doped Bi₂O₃–Co₃O₄/C: Oxygen vacancy-mediated band engineering and singlet oxygen pathway optimization - Xiaoqing Wang; Weiyi Li; Junhao Zhang; Jiangman Zheng; Tuo Li; Cong Du; Xuan Luo; Zhitao Ai; Chennan He; Shanjun Mao; Rongbo Zheng; Qing Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Three tetraspanins, Tspan1, Tspan2A and Tspan3 from Litopenaeus vannamei involved into Vibrio parahaemolyticus infection - Yi-Qian Zhang; Shuang-Shuang Luo; Xiu-Li Chen; Ai-Jin Wang; Chao-Jie Hou; Qing-Yun Liu; Min Peng; Chun-Ling Yang; Yan Lei; Wei-Lin Zhu; Hong Liu; Yong-Zhen Zhao; et al. (Fish & Shellfish Immunology, 2025)

Point-of-care testing of neuromyelitis optica spectrum disorder using a sonochemically enhanced bifunctional CdTe-ZIF-8 nanohybrids-labelled lateral flow immunoassay - Qing Fu; Manxia Wang; Jia Shu; Guangjun Xiao; Zhujun Ai; Xin Gao; Huan Cai; Yan Zhao; Xuhuai Fu; Zhizhong Li; Mengjie Zhang; Jinzhou Feng; et al. (Chemical Engineering Journal, 2025)

Comparative chloroplast genomic analysis: uncovering variations and phylogenetic relationships in tea plants from Shaoyang, Hunan Province, China - Jin Li; Yu Qin; Jun Tang; Xiao-Yan Qiu; Chang-Qing Xie; Han Tang; Ai-Ming Tang; Xiao Chen; Jun-Ping Xie; Hua Luo (Genetic Resources and Crop Evolution, 2025)

Generating vulnerability curves for seismic resilience assessment of steel pipe pile-supported wharves - Jingsong Huang; Lulu Zhang; Yunfan Zhang; Qing Ai (Ocean Engineering, 2025)

Polystyrene nanoplastics impair endometrial decidualization via cell cycle arrest and JNK-MAPK pathway-mediated oxidative stress in early pregnant mice - Jing-Ai Li; Li-Qing Wang; Qiong-Jun Xu; Xiao-Mei Wu; Xiao-Qing Pang; Jin-Xin He; Qian-Feng Qiao; Huang-Nian You; Yan-Chun Wu; Yong-Jiang Zhou (Food and Chemical Toxicology, 2025)

Deciphering the Role of Long Non-coding RNAs in Neural Differentiation and Reprogramming - Ziran Xu; Nianhong Lu; Jiangyuan Wang; Tianxue Yang; Mingfen Gao; Jing An; Xianglin Mei; Qing Ai (Stem Cell Reviews and Reports, 2025)

Flavoromics analysis and sensory evaluation of wines produced from nine red grape cultivars in Manas region, Xinjiang, China: Implications for terroir adaptation - Ning Shi; Yi-Fan Zhao; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Jia-Yi Deng; Jia-Yan Wei; Ai-Sai Chen; Chi-Fang Cheng; Shu-De Li; Fei He; Keji Yu; et al. (Food Chemistry, 2025)

Synergistic regulation of plant growth regulators on somatic embryogenesis and optimization of rejuvenation culture in Sinocrassula indica (Decne.) Berger - Li-qing Cheng; Shuang Liu; Heng-yu Huang; Ai-li Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Enantiomeric meroterpenoids from Rhododendron capitatum and their anti-inflammatory activity - Hang Xie; Qing Shi; Yu-Meng Miao; Xin-Yu Sun; Jin-Chang Huang; Chun Lei; Qing Mu; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Unraveling the effect of sorbitol on Cu-based catalysts for the continuous hydrogenation of CO2-derived ethylene carbonate to methanol and ethylene glycol - Tong-Yang Song; Ji-Zheng Zhang; Jun He; Xian-Lang Chen; Xin-Yuan Huang; Ai-Ping Jia; Xiaohong Li; Rong-Rong Li; Ji-Qing Lu (Chemical Engineering Journal, 2025)

Synergistic enhancement of wetland purification performance by introducing intermittent aeration and zero-valent iron under chilling stress - Lin-Yuan Wu; Bing-Xu Guo; Ke-Jia Zhang; Jun-Yu Ai; Wei-Yi Shi; Qing-Yuan Tian; Wen-Huai Wang; Jun-Feng Li (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Engineering Long-Acting apixaban loaded PLGA microspheres for the treatment of stroke caused by atrial fibrillation - Xue-Ai Liu; Yaseen Hussain; Jiawen Wang; Ping Xia; Xiang-Xiang Huang; Ming-Wei Huo; Ling-Zhi Shi; Jing-Hao Cui; Beom-Jin Lee; Renyu Huang; Yujin Ji; Minggang Wei; et al. (Chemical Engineering Journal, 2025)

Correlation and Path Analysis of Morphological Traits and Body Mass in Perca schrenkii - Qing Ji; Zhengwei Wang; Huale Lu; Huimin Hao; Syeda Maira Hamid; Qing Xiao; Wentao Zhu; Tao Ai; Zhaohua Huang; Jie Wei; Zhulan Nie (Fishes, 2025)
Perca schrenkii populations are experiencing significant declines, yet comprehensive morphological studies are still lacking. Understanding the relationship between morphological traits and body weight is crucial for conservation and breeding programs. We analyzed 13 morphological traits in 100 P. schrenkii specimens from Hamsigou Reservoir using correlation analysis, path analysis, and principal component analysis (PCA). Body weight exhibited the highest variability (CV = 39.76%). Strong correlations were observed between body weight and body length (R = 0.942), total length, and body width. A four-variable regression model explained 94.1% of body weight variation, with body length showing the strongest direct effect (path coefficient = 0.623). The first three principal components accounted for 76.687% of the total variance. Our findings demonstrate that BL, BW, BD, and ES can effectively predict body weight, providing valuable insights for the conservation and selective breeding of P. schrenkii.

Chemical constituents of Penicillium ferraniaense GE-7 and their cytotoxicities - Yan Wang; Shao-Hua Song; Lei-Ming Wu; Xue Zhou; Qing-Ren Lu; Ai-Ping Yin; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2025)

Machine learning strategy secures urban smart drinking water treatment plant through incremental advances - Yu-Qi Wang; Hong-Cheng Wang; Zi-Jie Xiao; Ling-Jun Bu; Jiuling Li; Xiao-Chi Feng; Bin Liang; Wen-Zong Liu; Fei-Yun Sun; Shi-Qing Zhou; Ai-Jie Wang (Water Research, 2025)

Analytical study on the backfill grouting in mitigation of vibrations from a tunnel embedded in a half-space - Fan Li; Hui Wang; Yingyi Wang; Chong Li; Qing Ai; Xingchun Huang (Tunnelling and Underground Space Technology, 2025)

Insights into the synergistic effects of exogenous glycine betaine on the multiphase metabolism of oxyfluorfen in Oryza sativa for reducing environmental risks - Zhao Jie Chen; Xu Zhen Shi; Ya Nan Qu; Si Ying Li; Gan Ai; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xuesheng Li; Yan Hui Wang (Journal of Hazardous Materials, 2025)

Phenol-driven ammonium recovery from coal chemical wastewater in a bioelectrochemical system (BES) - Ran Zeng; Li-Hui Yang; Si-Yuan Zhai; Cheng-Yan Liu; Na Lin; Qing-Hua Ou-Yang; Yan-Hua Xu; Ai-Jie Wang; Hao-Yi Cheng (Journal of Hazardous Materials, 2025)

Interaction between piles and layered fractional viscoelastic soils considering groundwater level - Zhi Yong Ai; He Wei Kuang; Zi Kun Ye; Qing Song Lu (Computers and Geotechnics, 2025)

Characteristics and plausible formation mechanisms of secondary inorganic and organic aerosols in four seasons and during haze episodes in Beijing - Yuewei Sun; Qing Yu; Weihua Qin; Yuepeng Zhang; Ke Xin; Jing Ai; Jing Chen (Atmospheric Research, 2025)

Five brasilane-type sesquiterpenoids with neuroprotective activities from Xylaria nigripes - Hong-Ping Long; Xi Zhou; Si-Qian Zhou; Lan-Qing Li; Ai-Lin Liang; Wen-Yu Lu; Wen-Xuan Wang; Shao Liu; Jing Li; Ji-Kai Liu (Phytochemistry, 2025)

Genome-wide identification and expression of Oryza sativa haloacid dehalogenase genes associated with oxadiazon metabolism - Zhao Jie Chen; Ya Nan Qu; Jun Jin Lu; Si Ying Li; Gan Ai; Xu Zhen Shi; Li Qing Zeng; Xiao Liang Liu; Dan Lu (Genetic Resources and Crop Evolution, 2025)

Synergistic enhancement of catalytic hydrodeoxygenation performance by oxygen vacancies and frustrated Lewis pairs - Qing-Qing Sun; Cong Liu; Guo-Qiang Zhang; Zhong-Qiu Liu; Mei-Ying Wang; Ai-Min Wang; Yujing Liu; Runpu Shen; Anguo Ying (Fuel, 2025)

Self-assembled preparation of wheat germ gliadin and (−)-epigallo-catechin 3-gallate nanoparticles: Structural characterization, formation mechanism and bioactivity - Zhi-Tong Zhu; Zhi-Rui Ding; Yu-Qing Liu; Ying Zhang; Jian-Zheng Li; Si-Yi Han; Xian-Ming Liu; Ming Hui; Na Liu; Ai-Mei Liao (Food Bioscience, 2025)

Optimized near infrared reflectance model based on preprocessing selection strategy for rapid analysis of 2-acetyl-1-pyrroline content in rice flour - Li-Hong Xie; Shao-Qing Tang; Gao-Neng Shao; Zhong-Hua Sheng; Shi-Kai Hu; Xiang-Jin Wei; Gui-Ai Jiao; Ling Wang; Pei-Song Hu (Food Control, 2025)

High performance piperidinium based anion exchange membranes with different twisted backbone structures for fuel cells - Ying Jie Liu; Guo Liang Zhang; Yong Qi Hu; Hui Peng; Li Wei Lai; Ai Mei Zhu; Qiu Gen Zhang; Qing Lin Liu (Chemical Engineering Journal, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Bimetallic RuCo anchored CoFe2O4 nanosheets to realize in-depth electronic modulation for boosted structural reconstruction and efficient seawater electrolysis - Xueling Wei; Youjun Huang; Qiguan Wang; Linlin Dang; Kai Zhang; Qing Guo; Wenhu Li; Taotao Ai; Sumin Wang (Chemical Engineering Journal, 2025)

An fusaric acid-based CRISPR library screen identifies MDH2 as a broad-spectrum regulator of Fusarium toxin-induced cell death - Wei-Tao Shi; Chun-Peng Yao; Wen-Hua Liu; Wan-Yi Cao; Wei Shao; Shen-Quan Liao; Ting Yu; Qing-Feng Zhu; Zhuang Chen; Ying-Jie Zang; Muhammad Farooq; Wen-Kang Wei; et al. (Journal of Hazardous Materials, 2024)

Blood cadmium levels and overactive bladder in middle-aged and older adults in the United States: Insights from NHANES 2007–2020 data - Fan Gao; Yin Lu; Qiang Cheng; Qing Ai; Bin Jiang; Zhen-Jun Luo; Guo-Rong Yang; Kai-Kai Lv; Qing Yuan; Hong-Zhao Li (Environmental Pollution, 2024)

The impact of nitrogen Fertilizer application on air Pollution: Evidence from China - Hong-shan Ai; Bo Fan; Zheng-qing Zhou; Jianhui Liu (Journal of Environmental Management, 2024)

Identification, functional analysis of chitin-binding proteins and the association of its single nucleotide polymorphisms with Vibrio parahaemolyticus resistance in Penaeus vannamei - Shuang-Shuang Luo; Xiu-Li Chen; Ai-Jin Wang; Qing-Yun Liu; Min Peng; Chun-Ling Yang; Di-Gang Zeng; Yong-Zhen Zhao; Huan-Ling Wang (Fish & Shellfish Immunology, 2024)

Roles and fates of antibiotics in anaerobic digestion of waste activated sludge: Insights to pro- and re-duction of antibiotic resistance genes - Qing-Bin Meng; Zhang-Wei He; Wenjing Yang; Wen-Tao Li; Cong-Cong Tang; Ai-Juan Zhou; Yong-Xiang Ren; Wenzong Liu; Zhihua Li; Aijie Wang (Chemical Engineering Journal, 2024)

Nickel sulfide nanorods encapsulated in Nitrogen-Doped carbon on nickel foam in situ derived from Saccharomycetes cerevisiae for the selective oxidation of biomass - Hao Chen; Si-Ru Chen; Qing Yang; Le-Xing You; Qun-Feng Ye; Ai-Jun Wang; Dong-Hai Lin; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2024)

Nrf2 deficiency exacerbated pulmonary pyroptosis in maternal hypoxia-induced intrauterine growth restriction offspring mice - Dan Chen; Ling-yun Man; Ying-ying Wang; Wei-ying Zhu; Hui-min Zhao; Sheng-peng Li; Yan-li Zhang; Shuai-chao Li; Ya-xian Wu; Ling-Ai; Qing-feng Pang (Reproductive Toxicology, 2024)

Analysis of growth inhibition of continuously planted Casuarina equisetifolia in relation to characteristic soil microbial functions and nutrient cycling - Yu-Hua Wang; Lei Hong; Jian-Juan Li; Qing-Xu Zhang; Ai-Qi Wang; Shao-Xiong Lin; Ming-Yue Hu; Yi-Ling Chen; Wen-Xiong Lin; Hai-Bin Wang; Ze-Yan Wu (Applied Soil Ecology, 2024)

Two-stage surrogate modeling strategy for predicting foundation pit excavation-induced strata and tunnel deformation - Zihao Liu; Qian Fang; Yi Shen; Qing Ai; Hui Wang; Xingchun Huang; Yong Yuan (Tunnelling and Underground Space Technology, 2024)

Multi-omics insights into the function and evolution of sodium benzoate biodegradation pathway in Benzoatithermus flavus gen. nov., sp. nov. from hot spring - Chao-Jian Hu; Yi-Qing Lv; Wen-Dong Xian; Jian-Yu Jiao; Zheng-Han Lian; Sha Tan; Meng-Meng Li; Zhen-Hao Luo; Ze-Tao Liu; Ai-Ping Lv; Lan Liu; Mukhtiar Ali; et al. (Journal of Hazardous Materials, 2024)

Bond behavior between steel bar and strain-hardening fiber-reinforced cementitious composites under fatigue loading - Qing-Hua Li; Ai-Min Luo; Bo-Tao Huang; Guo-Zhong Wang; Shi-Lang Xu (Engineering Structures, 2024)

Some evidence supporting the use of optically pure R-(−)-diniconazole: Toxicokinetics and configuration conversion on chiral diniconazole - Haoran Li; Kai Liu; Alan Kueichieh Chang; Ying Pei; Jianxin Li; Jiao Ai; Wenbao Liu; Tingting Wang; Liuping Xu; Ruiyun Li; Qing Yu; Nan Zhang; et al. (Science of The Total Environment, 2024)

Pyrrhotites in asteroid 162173 Ryugu: Records of the initial changes on their surfaces with aqueous alteration - Hiroharu Yui; Shu-hei Urashima; Morihiko Onose; Mayu Morita; Shintaro Komatani; Izumi Nakai; Yoshinari Abe; Yasuko Terada; Hisashi Homma; Kazuko Motomura; Kiyohiro Ichida; Tetsuya Yokoyama; et al. (Geochimica et Cosmochimica Acta, 2024)

Colletotrichum fioriniae causing anthracnose of Macropanax rosthornii in China - Yang Zhang; Yan Fang; Rou Ye; Yu-Kun Qi; Xiao-Chen Cui; Ai-Xin Dong; Yong-Chun Zeng; Yu-Feng Dong; Qing-Hai Wang (Crop Protection, 2024)

Multi-defect risk evaluation method (MREM) for lifetime performance evolution of tunnel system - Yi Shen; Dawei Huang; Tao Liu; Qing Ai; Hehua Zhu (Tunnelling and Underground Space Technology, 2024)

Distinct changes of taste quality and metabolite profile in different tomato varieties revealed by LC-MS metabolomics - Wen-qiang Cai; Peng-fei Jiang; Yang Liu; Xiao-qing Miao; Ai-dong Liu (Food Chemistry, 2024)

Robust and efficient Iron-Based electrodes for hydrogen production from seawater at high current density above 1000 mA cm−2 - Xian Zhang; Huanyu Zhu; Ziteng Zuo; Mengtian Jin; Ouwen Peng; Qing Lian; Yulan Huang; Peng Cheng; Zhong Ai; Shengling Xiang; Abbas Amini; Shaoxian Song; et al. (Chemical Engineering Journal, 2024)

Synergistic signal amplification of ultrathin nanowire-like PtCoFeRuMo high-entropy nanozyme and Z-scheme WO3/ZnIn2S4 heterostructure for split-typed photoelectrochemical aptasensing of myoglobin - Fan Xu; Ben-Fang Xu; Qing-Ying Ai; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemical Engineering Journal, 2024)

Chromones from the endophytic fungus Bipolaris eleusines - Yin-Zhong Fan; Chun Tian; Shun-Yao Tong; Qing Liu; Fan Xu; Bao-Bao Shi; Hong-Lian Ai; Ji-Kai Liu (Phytochemistry, 2024)

Polyethyleneimine functionalized gold nanodendrites for gluconic acid electroreduction - Zhe Wang; Qing-Ling Hong; Zhou-Yingqi Qu; Feng Shi; Chong Zhang; Pu-Jun Jin; Pei Chen; Xuan Ai; Yu Chen (Chemical Engineering Journal, 2024)

Methionine redox regulation of actin-interacting proteins primarily governs antioxidative signaling and response to the salvianolic acid B treatment in EA.hy926 cells - Ai-Cheng Wang; Xiao-Ming Qi; Qing-Fang Li; Yi-Jia Feng; Yuan-Lin Zhang; Hui-Zhi Wei; Jin-Shan Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2024)

Pervasive aqueous alteration in the early Solar System revealed by potassium isotopic variations in Ryugu samples and carbonaceous chondrites - Yan Hu; Frédéric Moynier; Wei Dai; Marine Paquet; Tetsuya Yokoyama; Yoshinari Abe; Jérôme Aléon; Conel M. O'D. Alexander; Sachiko Amari; Yuri Amelin; Ken-ichi Bajo; Martin Bizzarro; et al. (Icarus, 2024)

Effects of yeast screened from traditional fermented milk on commercial fermented milk as adjunct flavor culture - Hai-yan Kang; Xiao-lin Ao; Qing Tang; Hongli Li; Yang Fan; Ai-ping Liu; Li-kou Zou; Shu-liang Liu; Yong Yang; Ning Zhao; Jian-long Li (Food Bioscience, 2024)

Ultrathin RhCu bimetallenes for the selective electro-oxidation of glycerol - Qing-Ling Hong; Yue Zhao; Xuan Ai; Yu Ding; Fu-Min Li; Pei Chen; Pu-Jun Jin; Yu Chen (Chemical Engineering Journal, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

Optimized formula for the hybrid abalone Haliotis discus hannai♀ × H. fulgens♂: Betaine supplementation increases the use of rice bran meal as a replacement for kelp - Yao-Bin Ma; Wei-Guang Zou; Yan-Bo Liu; Chun-Xiang Ai; Wei-Wei You; Huo-Qing Huang; Ye-Xiao Chen; Xuan Luo; Cai-Huan Ke (Aquaculture, 2024)

Thin film composite polyamide nanofiltration membranes with interlayer constructed with core-shell structured polystyrene-polyacrylamide nanospheres for antibiotics separation - Ben-Qing Huang; Hong-Guang Cui; Tian-Yun Feng; Cai-Ling Yuan; Ai-Lian Chang; Ming-Lu Shao; Chi-Fan Zhu (Journal of Water Process Engineering, 2024)

Effects of salinity on sulfur-dominated autotrophic denitrification microorganisms: Microbial community succession, key microorganisms and response mechanisms - Zhuo-Ran Li; Xue-Ning Zhang; Hong-Cheng Wang; Hao-Yi Cheng; Ai-Jie Wang; Yan-Qing Zhang; Chong-Wei Cui; Yi-Lu Sun (Chemical Engineering Journal, 2023)

Machine learning framework for intelligent aeration control in wastewater treatment plants: Automatic feature engineering based on variation sliding layer - Yu-Qi Wang; Hong-Cheng Wang; Yun-Peng Song; Shi-Qing Zhou; Qiu-Ning Li; Bin Liang; Wen-Zong Liu; Yi-Wei Zhao; Ai-Jie Wang (Water Research, 2023)

Tandem c-cl cleavage and oxidation over Pt/ZSM-5 catalysts for CH2Cl2 deep oxidation: Acidity – Redox synergy, rate – Limiting step, and catalyst stability - Yu-Kun Ma; Li-Li Xu; Long-Ren Ouyang; Lu-Lu Huang; Ai-Ping Jia; Yu Wang; Ji-Qing Lu (Chemical Engineering Journal, 2023)

Molecular mechanism of different flower color formation of Cymbidium ensifolium - Ye Ai; Qing-Dong Zheng; Meng-Jie Wang; Long-Wei Xiong; Peng Li; Li-Ting Guo; Meng-Yao Wang; Dong-Hui Peng; Si-Ren Lan; Zhong-Jian Liu (Plant Molecular Biology, 2023)

Adaptive super-twisting sliding mode attitude coordination control for spacecraft formation flying with actuator saturation - Chao Xiao; Yong Guo; Cheng-qing Xie; Ai-jun Li; Chang-qing Wang (Advances in Space Research, 2023)

PM 2.5 juvenile exposure–induced spermatogenesis dysfunction by triggering testes ferroptosis and antioxidative vitamins intervention in adult male rats - Xiang Liu; Yaya Ai; Mingchen Xiao; Cao Wang; Zhen Shu; Jia Yin; Yu Chu; Qing Xiao; Bin Liu (Environmental Science and Pollution Research, 2023)
PM2.5 derived from automobile exhaust can cause reproductive impairment in adult males, but the toxic effects of PM2.5 exposure on reproductive function in juvenile male rats and its relationship with ferroptosis have not been reported. In this paper, 30-day-old juvenile male Sprague-Dawley (SD) rats were divided into four groups (blank control, vitamin control, PM2.5, and PM2.5+Vitamin). The blank control group was fed normally, and the vitamin control group was given intragastric administration of vitamins in addition to normal feeding. PM2.5 was administered via tracheal intubation. When the rats were treated for 4 weeks until reaching the period of sexual maturity. A mating test was performed first, and then their testicular and epididymal tissues were studied. Compared with control rats, juvenile male rats exposed to PM2.5 showed a decreased sperm count and fertility rate, redox imbalance, damaged mitochondria, a metabolic disorder of intracellular iron ions, and a significant rise in ferroptosis during the period of sexual maturity. After antioxidative vitamins intervention, the redox imbalance, metabolic disorder of intracellular iron ions, and ferroptosis were all alleviated, leading to the following conclusions: after being exposed to PM2.5 from automobile exhaust, male juvenile rats during the period of sexual maturity have significantly decreased reproductive function. The reproductive toxicity of PM2.5 is closely related to oxidative stress and ferroptosis. In addition, ferroptosis decreases and reproductive function is recovered to some degree after antioxidative vitamins intervention. Graphical abstract

Chalcogen-modified copper-nitrogen co-doped carbon as a stable and efficient antimicrobial cathode catalyst for microbial fuel cells - Bi-Lin Lai; Hai-Xia Liao; Shu-Qi Zhou; Hui-Xu Wei; Ai-Yi Li; Nan Li; Zhao-Qing Liu (Journal of Environmental Chemical Engineering, 2023)

Defect-rich hierarchical porous carbon prepared by homogeneous activation for high performance capacitive deionization - Xinyi Gong; Shizhan Feng; Luxiang Wang; Dianzeng Jia; Nannan Guo; Mengjiao Xu; Lili Ai; Qingtao Ma; Qing Zhang; Zuyun Wang (Desalination, 2023)

Genesis of No. 2 orebody of the Jinchuan magmatic Ni-Cu-(PGE) sulfide deposit, NW China: New constraints from the newly discovered deep extension - Ting-Mao Long; Xie-Yan Song; Jian Kang; Qing-Lin Liang; Yong-Cai Wang; De-Xian Li; Qi-Xing Ai; Wen-De Suo; Jian-Quan Lu (Mineralium Deposita, 2023)

Mechanical Characteristics and Particle Breakage of Calcareous Sand under Quasi-One-Dimensional Impact Load - Zhen-Zhen Nong; Qing Wang; He-Ying Hou; Peng-Ming Jiang; Ai-Zhao Zhou (Journal of Marine Science and Engineering, 2023)
Calcareous sand, a type of marine sediment formed from the skeletal remains of marine life, exhibits unique characteristics such as high porosity and fragility due to its biological origin. Particle breakage is a key attribute of calcareous sand. Given that foundations on calcareous sand islands encounter various types of loads, including pile driving, aircraft loading, earthquakes, and tsunamis, it is imperative to investigate its mechanical properties and particle breakage under high strain rates. This study focuses on assessing the dynamic mechanical properties of calcareous sand under quasi-one-dimensional impact loads using split Hopkinson pressure bar (SHPB) tests. Three particle sizes of calcareous sand with different water contents, strain rates, and relative densities were examined. The particle fragmentation degree of each sand sample was also analyzed quantitatively. The results indicated that stress–strain curves progress through an elastic phase with rapid elevation, followed by a plastic stage with a slower increase under various factors. Within the plastic phase, there are multiple instances of stress drops and recoveries. The stress–strain curves generally decrease as particle size increases, concurrent with an increase in particle breakage. Moisture content has minimal impact on the stress–strain curve; a higher moisture content does correspond to reduced particle breakage. Both the maximum strain and peak stress increase as the strain rate increases, resulting in a higher relative crushing rate. The difference between stress–strain curves under different relative densities diminishes as particle size increases, and greater relative density leads to reduced particle breakage. Functional relationships among peak stress and strain rate, relative fragmentation rate and water content, strain rate and relative density, as well as relative density and peak stress are also established.

Comparative Analysis of the Expression of Resistance-Related Genes Respond to the Diversity Foliar Pathogens of Pseudostellaria heterophylla - Xiao-Ai Wang; Yanping Gao; Weike Jiang; Lu Wang; Hui Wang; Xiaohong Ou; Yang Yang; Honglin Wu; Lanping Guo; Tao Zhou; Qing-Song Yuan (Current Microbiology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Bidirectional crosstalk of the cAMP/ROS-dependent signaling pathways in inflammatory macrophage: An activation of formononetin - Lan-Fang Zhang; Xiao-Yan Zhang; Ai-Cheng Wang; Yi-Jia Feng; Xiao-Ming Qi; Yuan-Lin Zhang; Qing-Fang Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2023)

Low-photovoltage-loss pringting perovskite solar cells in ambient air through ink synergistic engineering - Yifan Lv; Kaiyu Wang; Ai Lan; Lingfeng Chao; Changshun Chen; Jinpei Wang; Qing Yao; Jianxin Chen; Tengfei Pan; Yajing Li; Hui Zhang; Yingdong Xia; et al. (Chemical Engineering Journal, 2023)

Neurotoxicological mechanisms of carbon quantum dots in a new animal model Dugesia japonica - Jing Kang; Qing Ai; Ang Zhao; Haijiao Wang; Xiangpeng Zhang; Yanli Liu; Lingke Zhang; Yuqing Liu (Ecotoxicology, 2023)

Mechanism of subsidence-buckling and instability of slopes in thick-layered rigid rock under mining - Jie Deng; Jian-jun Zhao; Qi-yi Lai; Ai-nong Li; Ming-li Xie; Qing-miao Li; Xiao Zhao (Journal of Mountain Science, 2023)

Damage identification method on shield tunnel based on PLSR and equivalent damage analysis - Zhi-guo Yan; Jian-tao Li; Yi Shen; Zi-qi Xiao; Qing Ai; He-hua Zhu (Tunnelling and Underground Space Technology, 2023)

Pollution characteristics and light-driven evolution of environmentally persistent free radicals in PM2.5 in two typical northern cities of China - Jing Ai; Weihua Qin; Jing Chen; Yuewei Sun; Qing Yu; Ke Xin; Huiying Huang; Lingyun Zhang; Mushtaq Ahmad; Xingang Liu (Journal of Hazardous Materials, 2023)

The bound polyphenols of foxtail millet (Setaria italica) inner shell inhibit breast cancer by promoting lipid accumulation-induced autophagic death - Li-chao Zhang; Ya-ning Liu; Xiao-qin La; Shuai-tao Li; Li-na Wen; Ting Liu; Han-qing Li; Ai-ping Li; Haitao Wu; Chang-xin Wu; Zhuo-yu Li (Food and Chemical Toxicology, 2023)

Durable dual-methylpiperidinium crosslinked poly(binaphthyl-co-terphenyl piperidinium) anion exchange membranes with high ion transport and electrochemical performance - Wei Ting Gao; Xue Lang Gao; Yvonne Shuen Lann Choo; Jia Jun Wang; Zhi Hong Cai; Qiu Gen Zhang; Ai Mei Zhu; Qing Lin Liu (Chemical Engineering Journal, 2023)

Unraveling the evolution of dissolved organic matter in full-scale A/A/O wastewater treatment process using size exclusion chromatography with PARAFAC and nonnegative matrix factorization analysis - Min-Hui Cai; Ye-Chao Tian; Ai-Min Li; Yan Li; Yu-Ze Han; Wen-Xiang Ji; Qing Zhou; Jun Li; Wen-Tao Li (Water Research, 2023)

Effect of flavonoids and CYP3A4 variants on midostaurin metabolism - Ren-ai Xu; Qing-qing Li; Nan-yong Gao; Jing Wang; Xin-yue Li; Feng Ye; Jin-huan Ni; Guo-xin Hu; Jian-chang Qian (Food and Chemical Toxicology, 2023)

Brain Inflammatory Marker Abnormalities in Major Psychiatric Diseases: a Systematic Review of Postmortem Brain Studies - Yang-wen Ai; Yang Du; Lei Chen; Shu-Han Liu; Qing-shan Liu; Yong Cheng (Molecular Neurobiology, 2023)

Ecotoxicity stress and bioaccumulation in Eisenia fetida earthworms exposed to vanadium pentoxide in soil - Shi-qing Zhao; Hong Ni; Ji Li; Shun-hao Ai; Xiao-nan Wang; Xiang-yun Gao; Qian-yun Xu; Zheng-tao Liu (Environmental Science and Pollution Research, 2023)

Interactive effects of diet and water temperature on the nutritional value, flavor, and sensory quality in hybrid abalone (Haliotis. discus hannai ♀ × H. fulgens♂) meat - Yao-Bin Ma; Wei-Guang Zou; Chun-Xiang Ai; Xuan Luo; Sheng-Tai Liu; Huo-Qing Huang; Ye-Xin Chen; Wei-Wei You; Cai-Huan Ke (Aquaculture, 2023)

Simultaneous determination of dissolved organic nitrogen, nitrite, nitrate and ammonia using size exclusion chromatography coupled with nitrogen detector - Wen-Xiang Ji; Ye-Chao Tian; Min-Hui Cai; Bi-Cun Jiang; Shi Cheng; Yan Li; Qing Zhou; Bo-Qiang Li; Bai-Yang Chen; Xing Zheng; Wen-Tao Li; Ai-Min Li (Journal of Environmental Sciences, 2023)

Co-substrate promoting the biodegradation of refractory DOM in semi-coking wastewater: DOM evolution and microbial community - Min-Hui Cai; Ye-Chao Tian; Ai-Min Li; Yan Li; Yu-Ze Han; Jun Li; Hong-Fang Sun; Xin Wang; Qing Zhou; Wen-Tao Li (Journal of Environmental Chemical Engineering, 2023)

Impacts of extreme weather events on terrestrial carbon and nitrogen cycling: A global meta-analysis - Qing Qu; Hongwei Xu; Zemin Ai; Minggang Wang; Guoliang Wang; Guobin Liu; Violette Geissen; Coen J. Ritsema; Sha Xue (Environmental Pollution, 2023)

Water microecology is affected by seasons but not sediments: A spatiotemporal dynamics survey of bacterial community composition in Lake Changshou—The largest artificial lake in southwest China - Ai-ling Chen; Fu-qing Xu; Xia Su; Fu-pan Zhang; Wan-chao Tian; Shang-jie Chen; Fang Gou; Zhi-lin Xing; Jin-xin Xiang; Juan Li; Tian-tao Zhao (Marine Pollution Bulletin, 2023)

Integrated waterproofing evaluation method for longitudinal joints of shield tunnel subjected to extreme surcharge: Numerical analysis and experimental validation - Qing Ai; Yining Gu; Yong Yuan; Xiaomo Jiang; Hui Wang; Haitao Yu; Yongjie Huang (Tunnelling and Underground Space Technology, 2023)

PGC-1α/NRF1-dependent cardiac mitochondrial biogenesis: A druggable pathway of calycosin against triptolide cardiotoxicity - Xiao-Ming Qi; Yuan-Biao Qiao; Yuan-Lin Zhang; Ai-Cheng Wang; Jin-Hong Ren; Hui-Zhi Wei; Qing-Shan Li (Food and Chemical Toxicology, 2023)

Association between ambient carbon monoxide levels and hospitalization costs of patients with myocardial infarction: Potential effect modification by ABO blood group - Qing-Song Huang; Lai-Xin Zhou; Li-Li Yang; Yue-Xu Jiang; Hua Xiao; Da-Wei Li; Yu-Meng Zhou; Yue-Gu Hu; Na Li; Ya-Fei Li; Ai-Ling Ji; Peng Luo; et al. (Environmental Research, 2023)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

The association between short-term ambient sulfur dioxide exposure and hospitalization costs of ischemic stroke: a hospital-based study in Chongqing, China - En-Jie Tang; Yu-Meng Zhou; Li-Li Yang; Nan Wang; Yue-Xu Jiang; Hua Xiao; Yue-Gu Hu; Da-Wei Li; Na Li; Qing-Song Huang; Ning Du; Ya-Fei Li; et al. (Environmental Science and Pollution Research, 2022)

Gastrodin Attenuates Lipopolysaccharide-Induced Inflammatory Response and Migration via the Notch-1 Signaling Pathway in Activated Microglia - Yue-yi Yao; Run Li; Yan-ji Guo; Yu Zhao; Jia-zhi Guo; Qing-long Ai; Lian-mei Zhong; Di Lu (NeuroMolecular Medicine, 2022)

Invasibility and recoverability of a plant community following invasion depend on its successional stages - Hongwei Xu; Zemin Ai; Qing Qu; Minggang Wang; Guobin Liu; Sha Xue (Soil Ecology Letters, 2022)

Qipengyuania thermophila sp. nov., isolated from a Chinese hot spring - Zi-Yu Zhao; Ting-Ting Xia; Jian-Yu Jiao; Lan Liu; Qing-Yang Su; Meng-Meng Li; Ai-Ping Lv; Yu-Ting Ouyang; Wen-Jun Li; Hong Ming (Archives of Microbiology, 2022)

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

Cellular Apoptosis Induced by Deoxynivalenol - Qing’ai Chen; Ying Cui; Jiaru Zhao; Wanlin Zeng; Ni Jin; Lan Yang; Jun Yuan (Indian Journal of Microbiology, 2022)

Synthesis and evaluation of mycophenolic acid derivatives as potential anti-Toxoplasma gondii agents - Fan-Fan Shang; Mei-Yuan Wang; Jiang-Ping Ai; Qing-Kun Shen; Hong-Yan Guo; Chun-Mei Jin; Fen-Er Chen; Zhe-Shan Quan; Lili Jin; Changhao Zhang (Medicinal Chemistry Research, 2021)

Identification and characterization of Colletotrichum gloeosporioides sensu stricto, the agent of anthracnose disease of Sorbaria sorbifolia in China - Qing-Hai Wang; Xiang-Ying Li; Ting-Ting Xu; Meng-Ai Zhang; Yu-Hui Yang; Pei-Bo Feng; Su-Su Fan; Zhen-Yu Liu (Journal of General Plant Pathology, 2021)

Cyclocarioside O-Q, three novel seco -dammarane triterpenoid glycosides from the leaves of Cyclocarya paliurus - Tong-Yao Xuan; Jie Tan; Hui-Hui Sun; Can Yang; Wen-Yan Lv; Ji-Hua Zhang; Ke-Qing Zhang; Ze-Qun Nie; Zi-Jun Ye; Xiao-Ai He; Gang-Zhi Zhu; Kang-Ping Xu (Natural Product Research, 2021)

Long-term impact of accidental pollution on the distribution and risks of metals and metalloids in the sediment of the Longjiang River, China - Qian-Li Ma; Ling-Ai Yao; Qing-Wei Guo; Guang-Jie Zhou; Rong-Chang Liang; Qiao-Li Fang; Zhen-Cheng Xu; Xue-Min Zhao (Environmental Science and Pollution Research, 2021)

Effects of Enzymatic Hydrolysate of Oyster on Erectile Function in Male Hemicastrated Rats - Hai-Yan Wang; Zheng Yan; Shuang Liu; Ai-Qing Liu; Jun-She Sun (International Journal of Peptide Research and Therapeutics, 2020)

Identification of progranulin as a novel diagnostic biomarker for early-onset sepsis in neonates - Kai-Di Yang; Yu He; Sa Xiao; Qing Ai; Jia-Lin Yu (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Drug Elimination Alteration in Acute Lymphoblastic Leukemia Mediated by Renal Transporters and Glomerular Filtration - Yue Zhou; Bin Du; Min Kan; Shang Chen; Bo-Hao Tang; Ai-Qing Nie; Pan-Pan Ye; Hai-Yan Shi; Guo-Xiang Hao; Xiu-Li Guo; Qiu-Ju Han; Yi Zheng; et al. (Pharmaceutical Research, 2020)

Angiotensin Type 1 Receptors and Superoxide Anion Production in Hypothalamic Paraventricular Nucleus Contribute to Capsaicin-Induced Excitatory Renal Reflex and Sympathetic Activation - Yun Qiu; Fen Zheng; Chao Ye; Ai-Dong Chen; Jue-Jin Wang; Qi Chen; Yue-Hua Li; Yu-Ming Kang; Guo-Qing Zhu (Neuroscience Bulletin, 2020)

Blockade of c-Src Within the Paraventricular Nucleus Attenuates Inflammatory Cytokines and Oxidative Stress in the Mechanism of the TLR4 Signal Pathway in Salt-Induced Hypertension - Qing Yang; Xiao-Jing Yu; Qing Su; Qiu-Yue Yi; Xin-Ai Song; Xiao-Lian Shi; Hong-Bao Li; Jie Qi; Guo-Qing Zhu; Yu-Ming Kang (Neuroscience Bulletin, 2020)

Phenotypic, genetic, and molecular function of msc-2, a genic male sterile mutant in pepper (Capsicum annuum L.) - Qing Cheng; Ting Li; Yixin Ai; Qiaohua Lu; Yihao Wang; Lang Wu; Jinqiu Liu; Liang Sun; Huolin Shen (Theoretical and Applied Genetics, 2020)

Aliphatic suberin confers salt tolerance to Arabidopsis by limiting Na+ influx, K+ efflux and water backflow - Pei Wang; Chun-Mei Wang; Li Gao; Yan-Nong Cui; Hai-Li Yang; Nayana D. G. de Silva; Qing Ma; Ai-Ke Bao; Timothy J. Flowers; Owen Rowland; Suo-Min Wang (Plant and Soil, 2020)

Chemical Stimulation of Renal Tissue Induces Sympathetic Activation and a Pressor Response via the Paraventricular Nucleus in Rats - Chao Ye; Yun Qiu; Feng Zhang; Ai-Dong Chen; Hong Zhou; Jue-Jin Wang; Qi Chen; Yue-Hua Li; Yu-Ming Kang; Guo-Qing Zhu (Neuroscience Bulletin, 2020)

Knockdown of CaHSP60-6 confers enhanced sensitivity to heat stress in pepper (Capsicum annuum L.) - Saeed ul Haq; Abid Khan; Muhammad Ali; Wen-Xian Gai; Huai-Xia Zhang; Qing-Hui Yu; Sheng-Bao Yang; Ai-Min Wei; Zhen-Hui Gong (Planta, 2019)

Activation of anthrachamycin biosynthesis in Streptomyces chattanoogensis L10 by site-directed mutagenesis of rpoB - Zi-yue Li; Qing-ting Bu; Jue Wang; Yu Liu; Xin-ai Chen; Xu-ming Mao; Yong-Quan Li (Journal of Zhejiang University-SCIENCE B, 2019)

Impact of market misallocations on green TFP: evidence from countries along the Belt and Road - Qing Zhang; Fenghao Yan; Ke Li; Hongshan Ai (Environmental Science and Pollution Research, 2019)

Genomic identification of AP2/ERF transcription factors and functional characterization of two cold resistance-related AP2/ERF genes in celery (Apium graveolens L.) - Meng-Yao Li; Jie-Xia Liu; Jian-Nan Hao; Kai Feng; Ao-Qi Duan; Qing-Qing Yang; Zhi-Sheng Xu; Ai-Sheng Xiong (Planta, 2019)

The absolute configuration of anti-Vibrio citrinin dimeric derivative by VCD, ECD and NMR methods - Fei Cao; Tian-Tian Sun; Jian-Kun Yang; Guo-Zheng Zhao; Qing-Ai Liu; Lian-Dong Hu; Zheng-Yue Ma; Hua-Jie Zhu (Natural Product Research, 2019)

Identification and complete genome characterization of human enterovirus 117 from a child with pneumonia in China - Juan Du; Teng Zhu; Lu Zhuang; Pan-He Zhang; Xiao-Ai Zhang; Qing-Bin Lu; Wei Liu (Archives of Virology, 2019)

CaHSP16.4, a small heat shock protein gene in pepper, is involved in heat and drought tolerance - Liu-Jun Huang; Guo-Xin Cheng; Abid Khan; Ai-Min Wei; Qing-Hui Yu; Sheng-Bao Yang; De-Xu Luo; Zhen-Hui Gong (Protoplasma, 2019)

Transcriptome-Based Identification of a Strong Promoter for Hyper-production of Natamycin in Streptomyces - Kai Wang; Xiao-Fang Liu; Qing-Ting Bu; Yang Zheng; Xin-Ai Chen; Yong-Quan Li; Xu-Ming Mao (Current Microbiology, 2019)

AgMYB2 transcription factor is involved in the regulation of anthocyanin biosynthesis in purple celery (Apium graveolens L.) - Kai Feng; Jie-Xia Liu; Ao-Qi Duan; Tong Li; Qing-Qing Yang; Zhi-Sheng Xu; Ai-Sheng Xiong (Planta, 2018)

Spatial association between landslides and environmental factors over Guizhou Karst Plateau, China - Xi-liu Yue; Shao-hong Wu; Mei Huang; Jiang-bo Gao; Yun-he Yin; Ai-qing Feng; Xiao-ping Gu (Journal of Mountain Science, 2018)

Ecological vulnerability analysis of Tibetan towns with tourism-based economy: a case study of the Bayi District - Ai-ke Kan; Guo-qing Li; Xiao Yang; Ye-long Zeng; Luobu Tesren; Jie He (Journal of Mountain Science, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Genetic analysis of three porcine bocaparvoviruses and identification of a natural recombinant breakpoint in NS1 - Yu Zhou; Jia Xu; Shi-Kang Zhu; Qing-Feng Meng; Zhi-Xiong Lin; Ru Chen; Ai-Dong Qian (Archives of Virology, 2018)

Sphingorhabdus buctiana sp. nov., isolated from fresh water, and reclassification of Sphingopyxis contaminans as Sphingorhabdus contaminans comb. nov. - Hanyi Chen; Ai-Lian Piao; Xu Tan; Yuichi Nogi; Jina Yeo; Han Lu; Qing-Qing Feng; Jie Lv (Antonie van Leeuwenhoek, 2018)

Soil physical properties response to tillage practices during summer fallow of dryland winter wheat field on the Loess Plateau - Jian-Fu Xue; Ai-Xia Ren; Hui Li; Zhi-Qiang Gao; Tian-Qing Du (Environmental Science and Pollution Research, 2018)

Two new stilbene trimers from Cynodon dactylon - Bi-Jun Li; Yao Liu; Ai-Tong Gu; Qing Zhang; Lei Chen; Shu-Mei Wang; Feng Wang (Natural Product Research, 2017)

20(S)-25-methoxyl-dammarane-3β, 12β, 20-triol negatively regulates activation of STAT3 and ERK pathways and exhibits anti-cancer effects in HepG2 cells - Hui-Han Ai; Zi-Long Zhou; Lu-Guo Sun; Mei-Ting Yang; Wei Li; Chun-Lei Yu; Zhen-Bo Song; Yan-Xin Huang; Yin Wu; Lei Liu; Xiao-Guang Yang; Yu-Qing Zhao; et al. (Apoptosis, 2017)

Association between hyperhomocysteinemia and stroke with atherosclerosis and small artery occlusion depends on homocysteine metabolism-related vitamin levels in Chinese patients with normal renal function - Guan-Hui Wu; Fan-Zhen Kong; Xiao-Feng Dong; De-Feng Wu; Qian-Zhu Guo; Ai-Rong Shen; Qing-Zhang Cheng; Wei-Feng Luo (Metabolic Brain Disease, 2017)

Alismol, a Sesquiterpenoid Isolated from Vladimiria souliei, Suppresses Proinflammatory Mediators in Lipopolysaccharide-Stimulated Microglia - Dongdong Shi; Xiaoqiang Song; Yuanqiang Guo; Jing Xu; Yu Liu; Jingling Zhang; Chun-Ai Cui; Da-Qing Jin (Journal of Molecular Neuroscience, 2017)

Detection of genotoxic effects of drinking water disinfection by-products using Vicia faba bioassay - Yu Hu; Li Tan; Shao-Hui Zhang; Yu-Ting Zuo; Xue Han; Na Liu; Wen-Qing Lu; Ai-Lin Liu (Environmental Science and Pollution Research, 2017)

A20 reduces lipid storage and inflammation in hypertrophic adipocytes via p38 and Akt signaling - Luoyan Ai; Xiaohan Wang; Zhiwei Chen; Qing Lin; Dazhi Su; Qingqing Xu; Changwei Wu; Xiaoke Jiang; Antao Xu; Zhuping Fan (Molecular and Cellular Biochemistry, 2016)

Inhibitory effect of Gardenblue blueberry (Vaccinium ashei Reade) anthocyanin extracts on lipopolysaccharide-stimulated inflammatory response in RAW 264.7 cells - Wei Xu; Qing Zhou; Yong Yao; Xing Li; Jiu-liang Zhang; Guan-hua Su; Ai-ping Deng (Journal of Zhejiang University-SCIENCE B, 2016)

Transcriptomic analysis of the succulent xerophyte Zygophyllum xanthoxylum in response to salt treatment and osmotic stress - Qing Ma; Ai-Ke Bao; Wei-Wei Chai; Wen-Ying Wang; Jin-Lin Zhang; Yi-Xiao Li; Suo-Min Wang (Plant and Soil, 2016)

Removal of fluorescent dissolved organic matter in biologically treated textile effluents by NDMP anion exchange process: efficiency and mechanism - Wen-Tao Li; Zi-Xiao Xu; Chen-Dong Shuang; Qing Zhou; Hai-Bo Li; Ai-Min Li (Environmental Science and Pollution Research, 2016)

Fatal pneumonia cases caused by human adenovirus 55 in immunocompetent adults - Shu-Yan Zhang; Yan-Ping Luo; Dou-Dou Huang; Hang Fan; Qing-Bin Lu; Ying Wo; Gang Chen; Xiao-Ai Zhang; Yan Li; Yi-Gang Tong; Wu-Chun Cao; Wei Liu (Infectious Diseases, 2016)

Cochliomycin A inhibits the larval settlement of Amphibalanus amphitrite by activating the NO/cGMP pathway - Kai-Ling Wang; Gen Zhang; Jin Sun; Ying Xu; Zhuang Han; Ling-Li Liu; Chang-Lun Shao; Qing-Ai Liu; Chang-Yun Wang; Pei-Yuan Qian (Biofouling, 2016)

The inward-rectifying K+ channel SsAKT1 is a candidate involved in K+ uptake in the halophyte Suaeda salsa under saline condition - Hui-Rong Duan; Qing Ma; Jin-Lin Zhang; Jing Hu; Ai-Ke Bao; Li Wei; Qian Wang; Sheng Luan; Suo-Min Wang (Plant and Soil, 2015)

Seroprevalence and risk factors of Mycobacterium avium subspecies paratuberculosis infection in domestic sika deer in China - Qing-Feng Meng; Ying Li; Fan Yang; Gui-Zhi Yao; Ai-Dong Qian; Wei-Li Wang; Wei Cong (Tropical Animal Health and Production, 2015)

Epidemical features of HAdV-3 and HAdV-7 in pediatric pneumonia in Chongqing, China - Ying Wo; Qing-Bin Lu; Dou-Dou Huang; Xiao-Kun Li; Chen-Tao Guo; Hong-Yu Wang; Xiao-Ai Zhang; Wei Liu; Wu-Chun Cao (Archives of Virology, 2015)

Potential Effects of Mina53 on Tumor Growth in Human Pancreatic Cancer - Xiao-ping Tan; Wei-guo Dong; Qing Zhang; Zi-rong Yang; Xiao-fei Lei; Ming-hua Ai (Cell Biochemistry and Biophysics, 2014)

Detection and complete genome characterization of human enterovirus 118 from children with acute respiratory disease in China - Qing-Bin Lu; Ying Wo; Hong-Yu Wang; Xiao-Ai Zhang; Dou-Dou Huang; Jin Zhao; En-Mei Liu; Wei Liu; Wu-Chun Cao (Virus Genes, 2014)

Chronic curcumin treatment normalizes depression-like behaviors in mice with mononeuropathy: involvement of supraspinal serotonergic system and GABAA receptor - Xin Zhao; Chuang Wang; Jun-Fang Zhang; Li Liu; Ai-Ming Liu; Qing Ma; Wen-Hua Zhou; Ying Xu (Psychopharmacology, 2014)

Effects of practical dietary protein to lipid levels on growth, digestive enzyme activities and body composition of juvenile rice field eel (Monopterus albus) - Xiao Ma; Yi Hu; Xiao-Qing Wang; Qing-Hui Ai; Zhi-Gang He; Fu-Xian Feng; Xiang-Yang Lu (Aquaculture International, 2014)

Effect of data homogenization on estimate of temperature trend: a case of Huairou station in Beijing Municipality - Lei Zhang; Guo-Yu Ren; Yu-Yu Ren; Ai-Ying Zhang; Zi-Ying Chu; Ya-Qing Zhou (Theoretical and Applied Climatology, 2014)

Phylogeography of Hipposideros armiger (Chiroptera: Hipposideridae) in the Oriental Region: the contribution of multiple Pleistocene glacial refugia and intrinsic factors to contemporary population genetic structure - Ai‐Qing Lin; Gabor Csorba; Lin‐Feng Li; Ting‐Lei Jiang; Guan‐Jun Lu; Vu Dinh Thong; Pipat Soisook; Ke‐Ping Sun; Jiang Feng (Journal of Biogeography, 2014)
Aim The goals of our study were to assess the population history and genetic structure of the widespread bat H ipposideros armiger , and to evaluate the effect of palaeoclimatic changes and dispersal patterns on this species. Location S outh C hina, mainland S outheast A sia and the S outh H imalayas. Methods We amplified two mitochondrial DNA (mt DNA ) regions (cyt b and D ‐loop) and seven nuclear microsatellite loci (n SSR s) from 216 individuals of H . armiger . To examine the evolutionary history of this species, we constructed maximum likelihood and Bayesian phylogenetic trees based on the two mt DNA regions. From the mt DNA and/or n SSR data, we assessed population genetic structure using analysis of molecular variance ( AMOVA ) and median‐joining network and structure analyses. We also estimated demographic history and gene flow using a B ayesian skyline plot and the program I Ma 2. Results Phylogenetic and median‐joining network analyses revealed that H . armiger comprises two distinct mt DNA clades divided into seven subclades. The results of AMOVA suggested strong population genetic structure based on mt DNA , but weak structure based on n SSR s. structure analysis identified three population clusters and also showed weak genetic structure at the nuclear level. Demographic analyses revealed two population expansion events c . 0.62 Ma and c . 0.25 Ma. The basic phylogeographical structure of H . armiger was established by 0.24 Ma. I Ma 2 analysis demonstrated that substantial gene flow has occurred between different regions since then. Additionally, non‐significant population structure and significant gene flow were detected between T aiwan and H ainan island populations and those from mainland C hina. Main conclusions Our results suggest that divergence and population expansion of H . armiger occurred in association with P leistocene climatic changes and that multiple refugia may have existed for this species. Post‐glacial male‐biased dispersal was likely to be the primary contributor to the contemporary genetic structure of H . armiger populations. Gene flow may have contributed greatly to the genetic structure of insular populations and populations from mainland C hina.

ZxSOS1 is essential for long-distance transport and spatial distribution of Na+ and K+ in the xerophyte Zygophyllum xanthoxylum - Qing Ma; Yi-Xiao Li; Hui-Jun Yuan; Jing Hu; Li Wei; Ai-Ke Bao; Jin-Lin Zhang; Suo-Min Wang (Plant and Soil, 2014)

Identification of 40k γ-secalin genes - PENG-FEI QI; QING CHEN; THÉRÈSE OUELLET; CHENG-XING LE; JIA AI; YU-MING WEI; JI-RUI WANG; YOU-LIANG ZHENG (Journal of Genetics, 2013)

Landscape pattern evolution processes of alpine wetlands and their driving factors in the Zoige Plateau of China - Jun-hong Bai; Qiong-qiong Lu; Jun-jing Wang; Qing-qing Zhao; Hua Ouyang; Wei Deng; Ai-nong Li (Journal of Mountain Science, 2013)

Formation of soluble microbial products (SMP) by activated sludge at various salinities - Yan Li; Ai-Min Li; Juan Xu; Wen-Wei Li; Han-Qing Yu (Biodegradation, 2013)

Photodegradation of Tri (2-chloroethyl) Phosphate in Aqueous Solution by UV/H2O2 - Xin-Chao Ruan; Rui Ai; Xiao Jin; Qing-Fu Zeng; Ze-Yu Yang (Water, Air, & Soil Pollution, 2013)

Molecular characterization and phylogenetic analysis of porcine epidemic diarrhea virus (PEDV) field strains in south China - Zhi-Li Li; Ling Zhu; Jing-Yun Ma; Qing-Feng Zhou; Yan-Hua Song; Bao-Li Sun; Rui-Ai Chen; Qing-Mei Xie; Ying-Zuo Bee (Virus Genes, 2012)

Effects of Schisandra sphenanthera extract on the blood concentration of tacrolimus in renal transplant recipients - Hua-Wen Xin; Qing Li; Xiao-Chun Wu; Yan He; Ai-Rong Yu; Lei Xiong; Ying Xiong (European Journal of Clinical Pharmacology, 2011)

Effects of dietary protein sources on feed intake, growth and plasma thyroid hormones levels of Japanese flounder (Paralichthys olivaceus) - Jun-Ming Deng; Kang-Sen Mai; Qing-Hui Ai; Wen-Bing Zhang; Wei Xu; Zhi-Guo Liufu (Aquaculture International, 2011)

Transgenic Brassica chinensis plants expressing a bacterial codA gene exhibit enhanced tolerance to extreme temperature and high salinity - Qing-bin Wang; Wen Xu; Qing-zhong Xue; Wei-ai Su (Journal of Zhejiang University-SCIENCE B, 2010)

Isolation and characterization of a gene encoding a polyethylene glycol-induced cysteine protease in common wheat - Qing-Wei Zang; Cai-Xiang Wang; Xu-Yan Li; Zhi-Ai Guo; Rui-Lian Jing; Jun Zhao; Xiao-Ping Chang (Journal of Biosciences, 2010)

Fractions and leaching characteristics of mercury in coal - Chun-Gang Yuan; Qing-Peng Li; Ya-Na Feng; Ai-Ling Chang (Environmental Monitoring and Assessment, 2010)

MicroRNA-17 post-transcriptionally regulates polycystic kidney disease-2 gene and promotes cell proliferation - Huan Sun; Qing-Wei Li; Xiao-Yan Lv; Jian-Zhong Ai; Qiu-Tan Yang; Jing-Jing Duan; Guo-Hui Bian; Yan Xiao; Yi-Dong Wang; Zheng Zhang; Yu-Hang Liu; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Expression, Purification and Molecular Structure Modeling of Thioredoxin (Trx) and Thioredoxin Reductase (TrxR) from Acidithiobacillus ferrooxidans - Yiping Wang; Xiaojian Zhang; Qing Liu; Chenbing Ai; Hongyu Mo; Jia Zeng (Current Microbiology, 2009)

Long-term administration of tempol attenuates postinfarct ventricular dysfunction and sympathetic activity in rats - Zhen Shi; Ai-Dong Chen; Yao Xu; Qi Chen; Xing-Ya Gao; Wei Wang; Guo-Qing Zhu (Pflügers Archiv - European Journal of Physiology, 2009)

Relationships between thiopurine S-methyltransferase polymorphism and azathioprine-related adverse drug reactions in Chinese renal transplant recipients - Hua-Wen Xin; Hui Xiong; Xiao-Chun Wu; Qing Li; Lei Xiong; Ai-Rong Yu (European Journal of Clinical Pharmacology, 2009)

Sample digestion for determining chloramphenicol residues in carp serum and muscle - Zhi-Yong Huang; Qing-Pi Yan; Qiang Zhang; Ai-Hong Peng (Aquaculture International, 2009)

Transformation of sugarcane with ACC oxidase antisense gene - Ai-Qin Wang; Wei-Qing Dong; Yuan-Wen Wei; Cheng-Mei Huang; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2009)

Analysis of bacterial communities associated with spores of Gigaspora margarita and Gigaspora rosea - Liangkun Long; Honghui Zhu; Qing Yao; Yuncan Ai (Plant and Soil, 2008)

Concentrations and bioaccessibility of polycyclic aromatic hydrocarbons in wastewater-irrigated soil using in vitro gastrointestinal test - Sardar Khan; Qing Cao; Ai-Jun Lin; Yong-Guan Zhu (Environmental Science and Pollution Research, 2008)

Altered gene expression of NIDD in dorsal root ganglia and spinal cord of rats with neuropathic or inflammatory pain - Meng-Ling Chen; Chun Cheng; Qing-Shan Lv; Zhi-Qin Guo; Ying Gao; Shang-Feng Gao; Xin Li; Shu-Qiong Niu; Shu-Xian Shi; Ai-Guo Shen (Journal of Molecular Histology, 2008)

Molecular Variability of Hop stunt viroid: Identification of a Unique Variant with a Tandem 15-nucleotide Repeat from Naturally Infected Plum Tree - Yuan-Ai Yang; Hong-Qing Wang; Zu-Jian Wu; Zhuo-Min Cheng; Shi-Fang Li (Biochemical Genetics, 2008)

Identification of defense-related genes in rice responding to challenge by Rhizoctonia solani - Chang-Jiang Zhao; Ai-Rong Wang; Yu-Jun Shi; Liu-Qing Wang; Wen-De Liu; Zong-Hua Wang; Guo-Dong Lu (Theoretical and Applied Genetics, 2008)

Increase of multi-metal tolerance of three leguminous plants by arbuscular mycorrhizal fungi colonization - Ai-Jun Lin; Xu-Hong Zhang; Ming-Hung Wong; Zhi-Hong Ye; Lai-Qing Lou; You-Shan Wang; Yong-Guan Zhu (Environmental Geochemistry and Health, 2007)

Proteomic identification of differently expressed proteins responsible for osteoblast differentiation from human mesenchymal stem cells - Ai-Xia Zhang; Wei-Hua Yu; Bao-Feng Ma; Xin-Bing Yu; Frank Fuxiang Mao; Wei Liu; Jia-Qing Zhang; Xiu-Ming Zhang; Shu-Nong Li; Ming-Tao Li; Bruce T. Lahn; Andy Peng Xiang (Molecular and Cellular Biochemistry, 2007)

Improved production of ethanol by deleting FPS1 and over-expressing GLT1 in Saccharomyces cerevisiae - Qing-Xue Kong; Ji-Guang Gu; Li-Min Cao; Ai-Li Zhang; Xun Chen; Xue-Ming Zhao (Biotechnology Letters, 2006)

Glucosamine sulfate–induced apoptosis in chronic myelogenous leukemia K562 cells is associated with translocation of cathepsin D and downregulation of Bcl-xL - Zhe Wang; Rong Liang; Gao-Sheng Huang; Ying Piao; Yong-Qing Zhang; Ai-Qin Wang; Bao-Xia Dong; Ji-Liang Feng; Guo-Rong Yang; Ying Guo (Apoptosis, 2006)

The involvement of chloroplast HSP100/ClpB in the acquired thermotolerance in tomato - Jin-ying Yang; Ying Sun; Ai-qing Sun; Shu-ying Yi; Jia Qin; Ming-hui Li; Jian Liu (Plant Molecular Biology, 2006)

Molecular marker application in sugarcane - Mu-Qing Zhang; Xue-Fang Zheng; Ai-Li Yu; Jing-Sheng Xu; Hui Zhou (Sugar Tech, 2004)